Preparation, mechanical properties and enhanced wear resistance of TiC-Fe composite cermet coating. (December 2021) - Xiao, Meng; Zhang, Yuanwei; Wu, Yaosha; Qiu, Zhaoguo; Zhou, Cheng; Zhuo, Shiye; Liu, Min; Zeng, Dechang
Abstract: TiC-Fe based cermet coating with high hardness and superior wear resistance together with low price and environmental friendliness was developed. Initially, the TiC-Fe composite particles were prepared by high energy ball milling, spray drying and plasma spheroidization. These cermet powders not only showed high sphericity and dense microstructure but also presented homogeneous distribution of TiC. Then, the TiC-Fe cermet coating was deposited by high velocity air fuel (HVAF). The results indicated that introducing ceramics would increase the deformation degree of the splats and eliminate the layered structure, which effectively enhanced the microhardness and wear resistance of composite coating. Compared with pure metallic coating, the microhardness of cermet coating increased to 887.5 HV0.3, while the wear rates of cermet coating reduced by 40% and 60% at 10 N and 25 N, respectively. Besides, the TiC-Fe cermet coating showed much less sensitive to the heavy load. The primary wear mechanism of single 316 L coating was a combination of adhesive wear and severe oxidation, while the TiC-Fe cermet coating showed slight abrasive wear combined with oxidation. The excellent wear resistance together with its harmless to human body make the TiC-Fe based composite coating a potential candidate when using at kitchen ware surface. Highlights: The dense and spherical TiC-Fe cermet particles were successfully prepared. TiC addition significantly reduced the porosity and increased the microhardness of coating. The developed TiC-Fe cermet coating exhibits excellent wear resistance.